Simulation of Single Electron Transistor in Multi-Level Mode Using Non-Equilibrium Green Function Method - Huỳnh Hoàng Trung; Lê Hoàng Minh; Đinh Sỹ Hiền (Journal of Technical Education Science, 2012)
Single electron transistor (SET) is a key element in our research field where device operation is based on one-by-one electron through the channel utilizing the Coulomb blockade effect. In this paper, we provide an overview of research developments of SET. This is achieved in this model by using Non-Equilibrium Green Function (NEGF) method to compute transport function, Coulomb oscillation, and ultimately the current-voltage characteristics. The simulation program is written by using graphic user guide (GUI) in MatLab. The effects of capacitance, bias, and temperature on current-voltage characteristics of SET are also presented.